Behavior genetics research on personality: Moving beyond traits to examine characteristic adaptations. Issue 8 (11th June 2021) - Nguyen, Phuong Linh L.; Syed, Moin; McGue, Matt
Abstract: This study argues that behavior genetics research on personality should expand beyond universal traits to include characteristic adaptations. Trait research examines broad, decontextualized, and universal domains such as the Five‐Factor Model. Characteristic adaptations are more contextualized than traits, such as goals and life strategies as responses to specific life demands. The study is organized into three sections: (1) a review of the abundance of behavior genetics research on personality traits, which has reached a convergent point at which few further findings are reported beyond the classic distribution of high genetic and non‐shared environmental influences with little to no shared environmental effect; (2) a review of existing behavior genetics research on characteristic adaptations that, although limited in volume, has demonstrated patterns far less consistent than traits; and (3) a discussion on future directions and important limitations to consider in conducting and interpreting behavior genetics research on non‐trait personality. The connection between characteristic adaptations and contextualized life outcomes, the preponderance of homogenous findings on traits, and the sparse yet promising findings of characteristic adaptations, all support the need for behavior genetics research on personality to expand beyond the broad trait level to characteristic adaptations and beyond.